The Impact of Tuberculosis on People Living With HIV: Scoping Review - Hulu, Victor Trismanjaya; Ginting, Rapael; Manalu, Putranto; Samosir, Frans Judea; Hartono; Siregar, Santy Deasy; Siagian, Masryna; Zendrato, Victorwan Novri; Sihotang, Widya Yanti (YCAB Publisher, 2024)
Background:Tuberculosis (TB) patients with HIV/AIDS experience higher mortality rates, lower cure rates, and poorer treatment adherence compared to TB patients without HIV. As a result, TB can exacerbate HIV progression and lead to increased mortality. This study aims to investigate and summarize the determinants of TB incidence among people living with HIV/AIDS. Objective:This study employs a scoping review approach to explore the key factors associated with TB occurrence in HIV/AIDS patients. Methods:A literature search was conducted across indexed databases, including Scopus, PubMed, Google Scholar, and Crossref. Studies published between 2013 and 2021 were selected based on article titles, study design, population, intervention, and results. Fourteen relevant articles were included. Data were processed by identifying key sentences relevant to the coding framework, highlighting important findings, and organizing a narrative review framework. Qualitative data analysis was performed using NVIVO-12 Plus, with data presentation and report compilation. Results:The study identifies age, gender, education and knowledge level, nutritional status, use of antiretroviral therapy (ART), and cluster of differentiation 4 (CD4) cell count as the dominant factors influencing TB incidence among people living with HIV/AIDS. Conclusion:HIV infection weakens the immune system by attacking lymphocytes, leaving individuals with HIV/AIDS highly susceptible to Mycobacterium tuberculosis infection. Keywords:tuberculosis; HIV; AIDS; ART; CD4